2007
DOI: 10.1016/j.rapm.2007.06.027
|View full text |Cite
|
Sign up to set email alerts
|

385: The anatomy of the thoracic spinal canal investigated with magnetic resonance imaging (MRI)

Abstract: : Background and Objectives : Anesthesiologists are reluctant to consider higher levels for spinal anesthesia, largely due to direct threats to the spinal cord. The goal of this study is to investigate, with magnetic resonance imaging (MRI), the distances between the relevant structures of the spinal canal (spinal cord, thecal tissue, etc.) to determine modal anatomical positions for neuraxial anesthesia. Method : A group of 19 patients were imaged with an MRI scanner in supine position. Medial sagittal slices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…5 Previous study by Lee et al found the similar result that the posterior duraspinal cord distance is significantly greater in the middle thoracic region than at upper and lower thoracic levels (e.g., T6 9.5 +/-1.8 mm, T12 3.7 +/-1.2 mm, T1 4.7 +/-1.7 mm. 6 We performed this procedure in the head-down sitting position. This position will make the posterior separation of the dura mater, and the spinal cord is increased compared with the supine and lateral positions.…”
Section: Discussionmentioning
confidence: 99%
“…5 Previous study by Lee et al found the similar result that the posterior duraspinal cord distance is significantly greater in the middle thoracic region than at upper and lower thoracic levels (e.g., T6 9.5 +/-1.8 mm, T12 3.7 +/-1.2 mm, T1 4.7 +/-1.7 mm. 6 We performed this procedure in the head-down sitting position. This position will make the posterior separation of the dura mater, and the spinal cord is increased compared with the supine and lateral positions.…”
Section: Discussionmentioning
confidence: 99%